1998
DOI: 10.1093/brain/121.4.611
|View full text |Cite
|
Sign up to set email alerts
|

The neural substrates of memory systems impairment in Alzheimer's disease. A PET study of resting brain glucose utilization

Abstract: Summary The aim of this study was to determine the neuronal basis for memory impairment in Alzheimer's disease by taking advantage of the clinical and metabolic heterogeneity of this pathology. To this end, 19 patients satisfying the NINCDS-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
183
0
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(212 citation statements)
references
References 113 publications
(168 reference statements)
22
183
0
6
Order By: Relevance
“…Interaction analyses revealed that a network including the left temporoparietal and inferior frontal regions was significantly less recruited in AD patients than in the control group, when comparing word to WL2 nonword conditions. This result is in keeping with previous neuroimaging findings showing a correlation between semantic deficits in AD patients and impairment of left temporoparietal areas, as measured by structural MRI or resting brain metabolism [Desgranges et al, 1998;Grossman et al, 1997Grossman et al, , 1998]. As suggested by Grossmann et al [2003], impaired activity in the left temporoparietal and frontal regions in AD patients could reflect impaired integration of lexicosemantic information, regardless of the domain of knowledge or the nature of the task.…”
Section: Cortical Activation For Lexicosemantic Representations In Adsupporting
confidence: 91%
See 2 more Smart Citations
“…Interaction analyses revealed that a network including the left temporoparietal and inferior frontal regions was significantly less recruited in AD patients than in the control group, when comparing word to WL2 nonword conditions. This result is in keeping with previous neuroimaging findings showing a correlation between semantic deficits in AD patients and impairment of left temporoparietal areas, as measured by structural MRI or resting brain metabolism [Desgranges et al, 1998;Grossman et al, 1997Grossman et al, , 1998]. As suggested by Grossmann et al [2003], impaired activity in the left temporoparietal and frontal regions in AD patients could reflect impaired integration of lexicosemantic information, regardless of the domain of knowledge or the nature of the task.…”
Section: Cortical Activation For Lexicosemantic Representations In Adsupporting
confidence: 91%
“…By contrast, brain regions underlying (sublexical) phonological levels of language processing are primarily located in the left (or bilateral) superior temporal area, and more specifically in the superior temporal sulcus and the posterior superior temporal gyrus; these regions are activated when participants listen to both meaningful and meaningless speech (e.g., nonwords), but not when listening to acoustically matched nonverbal sounds [Binder, 2000;Binder and Price, 2001;Binder et al, 2000;Burton et al, 2000Burton et al, , 2005Demonet et al, 1992Demonet et al, , 1994Hickok and Poeppel, 2000;Jacquemot et al, 2003;Jancke et al, 2002;Majerus et al, 2002;Mazoyer et al, 1993;Mummery et al, 1999;Perani et al, 1996;Poldrack et al, 2001;Specht and Reul, 2003]. In our study, on the basis of available neuroimaging studies that have studied language processing in AD, we expected decreased activation in left temporoparietal areas, as well as in the left lateral frontal cortex when AD patients had to repeat words and activate lexicosemantic levels of language representation [Desgranges et al, 1998;Grossman et al, 2003Grossman et al, , 2004Zahn et al, 2004]. With respect to phonological processing, we expected decreased activity (compared to elderly controls) in the posterior superior temporal gyrus and Broca's area when AD patients had to repeat nonwords, in line with previous structural neuroanatomical findings [Harasty et al, 2001].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In fact, it is one of the brain regions most affected by AD, even at the very early clinical manifestations of the disease (Salmon et al, 2008; for reviews, see Buckner, 2004 andSperling et al, 2010). PET studies showed that episodic memory retrieval is correlated with brain metabolism in the PCC in AD patients (Desgranges et al, 1998(Desgranges et al, , 2002, as well as in patients with MCI and questionable AD (Chételat et al, 2003;Salmon et al, 2008). More recently, Bastin et al (2010) showed that CER performance, as assessed by the PDP, was related to metabolism in the PCC in pre-dementia stage AD patients.…”
Section: Familiarity and Parietal Cortexmentioning
confidence: 99%
“…Resultant images were then smoothed using a classical Gaussian kernel of 14 mm, to blur individual variations and to increase the signal-to-noise ratio. In order to remove the confounding effect of intersubject variability in global CMRglc, the CMRGlc images were divided pixel by pixel by the individual value for the cerebellar vermis (this value being not statistically different from controls), as classically performed in previous studies [14,15,16,19]. .…”
Section: Image Handling and Transformationsmentioning
confidence: 99%